Application of polymer inclusion membrane to recover nickel and gold: A method to complement hydrometallurgical recycling of waste printed circuit boards - Jha, Rohit (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Metallurgical Engineering